2023
DOI: 10.1126/sciadv.adg1123
|View full text |Cite
|
Sign up to set email alerts
|

Light-activated macromolecular phase separation modulates transcription by reconfiguring chromatin interactions

Abstract: Biomolecular condensates participate in the regulation of gene transcription, yet the relationship between nuclear condensation and transcriptional activation remains elusive. Here, we devised a biotinylated CRISPR-dCas9–based optogenetic method, light-activated macromolecular phase separation (LAMPS), to enable inducible formation, affinity purification, and multiomic dissection of nuclear condensates at the targeted genomic loci. LAMPS-induced condensation at enhancers and promoters activates endogenous gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…A few key examples using in vitro reconstituted condensates have shown that biochemical activity (e.g., nucleation of actin and microtubule polymerization) is increased upon condensate formation ( 51 54 ). Cell-based approaches to investigate the link between condensates and gene transcription have mainly used engineered, synthetic, or otherwise artificial approaches at supraphysiological concentrations, leading to contradictory conclusions with some reporting no link ( 55 , 56 ) and others finding a link ( 57 , 58 ). Here, we show, at endogenous protein concentrations, in both COS-7 cells with a reporter gene and 10T1/2 cells with a cell identity gene, that the gene activation function of MYOCD is coupled to and requires its formation of condensates.…”
Section: Discussionmentioning
confidence: 99%
“…A few key examples using in vitro reconstituted condensates have shown that biochemical activity (e.g., nucleation of actin and microtubule polymerization) is increased upon condensate formation ( 51 54 ). Cell-based approaches to investigate the link between condensates and gene transcription have mainly used engineered, synthetic, or otherwise artificial approaches at supraphysiological concentrations, leading to contradictory conclusions with some reporting no link ( 55 , 56 ) and others finding a link ( 57 , 58 ). Here, we show, at endogenous protein concentrations, in both COS-7 cells with a reporter gene and 10T1/2 cells with a cell identity gene, that the gene activation function of MYOCD is coupled to and requires its formation of condensates.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic function of chromatin condensates in modulating gene expression is generally accepted and proved by recent publications. [ 95 ] However, other indications question this linear relationship. In this direction, it has recently been suggested that E–P loop strength and related microcompartments are not linearly connected with the transcriptional outputs.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, nuclear condensates themselves can reorganize the local chromatin architecture 66 . For example, it has been shown that TFs such as FOXA1 and SOX2 co-condense with DNA in vitro, exerting a tension force on the DNA strand which can bring together distal regions 67,68 .…”
Section: Transcriptional Hubs Condensates or Factories?mentioning
confidence: 99%